Febrile urinary tract infections in young children: recommendations for the diagnosis, treatment and follow-up. - Ammenti, Anita; Cataldi, Luigi; Chimenz, Roberto; Fanos, Vassilios; La Manna, Angela; Marra, Giuseppina; Materassi, Marco; Pecile, Paolo; Pennesi, Marco; Pisanello, Lorena; Sica, Felice; Toffolo, Antonella; et al. (Acta Paediatr, 2012)
UNLABELLED: We report the recommendations for the diagnosis, treatment, imaging evaluation and use of antibiotic prophylaxis in children with the first febrile urinary tract infection, aged 2 months to 3 years. They were prepared by a working group of the Italian Society of Pediatric Nephrology after careful review of the available literature and a consensus decision, when clear evidence was not available. CONCLUSION: These recommendations are endorsed by the Italian Society of Pediatric Nephrology. They can also be a tool of comparison with other existing guidelines in issues in which much controversy still exists.
Keywords: Anti-Bacterial Agents; Child, Preschool; Female; Fever; Follow-Up Studies; Humans; Infant; Male; Urinary Tract Infections